Righting miscarriages of justice?: ten years of the Criminal Cases Review Commission - Elks, Laurie (Justice, 2008)
The Commission's origins and powers -- The meaning of safety -- The approach to fresh evidence (1) - pendleton and after - The approach to fresh evidence (2) - expert evidence -- The approach to fresh evidence (3) - further considerations -- Modern standards of fairness -- Changes in the law -- Homicide cases -- Sexual offences cases -- Police and prosecution misconduct cases -- The commission in the magistrates' court -- The Commission's sentencing jurisdiction -- The Commission in Northern Ireland -- Three further topics - non-disclosure, the impact of the Human Rights Act and the significance of plea -- Reflections